2006
DOI: 10.1007/s00531-006-0118-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution of the Rides Prerifaines (Morocco): structural and seismic interpretation and analogue modelling experiments

Abstract: The Rides Prerifaines (RP) of Morocco constitute the leading edge of the Rif chain. They involve a Triassic-Palaeocene succession deposited on a peneplained Palaeozoic fold belt and accumulated in basins delimited by NE-SW-trending normal fault systems. A significant hiatus separates an overlying Middle Miocene-Upper Miocene foredeep sequence. The reconstruction of the complex structural evolution of the RP during the later compressive phases that affected the Rif chain since Middle Miocene time has been the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
87
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(99 citation statements)
references
References 23 publications
10
87
1
1
Order By: Relevance
“…Between 8 Ma and the latest Tortonian (~7.25 Ma), a marked switch occurred from basin subsidence to thick‐skinned contraction resulting in fault kinematics orientated N‐S to NE‐SW. Field and seismic evidence suggested that thrusting inverted Mesozoic normal faults in the African margin (Capella et al, ; Sani, Ventisette, Montanari, Bendkik, & Chenakeb, ). The latest Miocene contraction is orientated on average NNE‐SSW which is consistent with recent GPS motions for the western Rif (Koulali et al, ; Palano et al, ).…”
Section: Geodynamic Control On the Evolution Of The Atlantic‐mediterrmentioning
confidence: 99%
“…Between 8 Ma and the latest Tortonian (~7.25 Ma), a marked switch occurred from basin subsidence to thick‐skinned contraction resulting in fault kinematics orientated N‐S to NE‐SW. Field and seismic evidence suggested that thrusting inverted Mesozoic normal faults in the African margin (Capella et al, ; Sani, Ventisette, Montanari, Bendkik, & Chenakeb, ). The latest Miocene contraction is orientated on average NNE‐SSW which is consistent with recent GPS motions for the western Rif (Koulali et al, ; Palano et al, ).…”
Section: Geodynamic Control On the Evolution Of The Atlantic‐mediterrmentioning
confidence: 99%
“…The total thickness of the post-orogenic cover reaches up to 2500 m, both in wedge-top and foredeep settings (e.g., Wernli, 1988;Flinch, 1993;Samaka et al, 1997;Sani et al, 2000Sani et al, , 2007. This post-orogenic cover mostly consists of siliciclastic, marl-sandstone alternations called the "Blue Marls or Blue Marl Formation" in recent literature (Benson et al, 1991;Hilgen et al, 2000a;Sani et al, 2007), and Marnes Bleues du Maroc, or Néogène post-nappes in earlier publications (e.g., Feinberg, 1986;Wernli, 1988). This clastic succession also includes, at limited locations, the products of carbonate factories.…”
Section: Palaeogeography and Geological Backgroundmentioning
confidence: 99%
“…Its sedimentary remnants were incorporated in the Rif thrust-systems (Morley, 1988(Morley, , 1992Chalouan et al, 2008) during the orogenic phase that ceased in the late Tortonian creating the Betic-Rif arc (Jolivet et al, 2006;Vergés and Fernàndez, 2012;van Hinsbergen et al, 2014;Do Couto et al, 2016;Crespo-Blanc et al, 2016). In Morocco, several lines of evidence suggest that the last pulse of Miocene nappestacking occurred during the middle-late Tortonian in a submerged foreland, which gradually shifted south to south-westward as a result of flexure caused by the Prerif (= Prerifaine) Nappe emplacement, the frontal part of the orogenic wedge (e.g., Suter, 1980;Feinberg, 1986;Flinch, 1993;Gomez et al, 2000;Zouhri, 2002;Sani et al, 2007;Capella et al, 2017b). The submarine character of this event is deduced from the presence of Middle Miocene planktic foraminiferal assemblages found in mudstones that are mixed with the Prerif Nappe (Leblanc, 1979;Feinberg, 1986).…”
Section: Linking the Early And Middle Miocene To The Late Miocene Conmentioning
confidence: 99%
“…Thus this strong correlation existing between magnetic anomalies and the regional structures shows that this digital mapping based on an aeromagnetic survey can be used for other regions where access is difficult, in order to apply some corrections to various existing geologic maps. Field data permit locating the detected features corresponding to NE to SW-trending folds characteristic of the Paleozoic basement (Durand-Delga et al 1960-1962Faugères 1978;Ait Brahim 1983;Leblanc and Olivier 1984;Hoepffner 1994;Haddaoui 2000;Ben Abbou 2001;Zizi 2002;Moratti et al 2003;Moratti and Chalouan 2007;Sani et al 2007;Habibou et al 2012;Ouarhache et al 2012) and verifying the existence of the NE-SW fault system, corresponding essentially to normal faults, inherited from the Late Variscan. It should be pointed out that even with this strong correlation of processed magnetic maps with field geology, it was not possible to detect some of the folded basaltic sills occurring in this region, probably because of their small thickness and the spacing of flight lines (500 m).…”
Section: Resultsmentioning
confidence: 99%